دوافع تعرض الم أ رة الماكثة في البيت للقنوات الفضائية الخاصة - غلام خديجة; قاسمي حنان; د/عطاء الله طريف (جامعة عمار ثليجي الاغواط, 2023)
مخلص الد ا رسة: هدددفت د ا رسدتنا الدى التعدرف علدى دوافدع تعدرل المد أ رة الماكثددة فدي البيدت للقندوات نموذجا ؟ Samira tv الفضائية الخاصة وجاءت هذه قناة وانطلقت الد ا رسة من إشكالية ما دوافع تعرل الم أ رة الماكثة في البيت للقناة الفضائية ؟ Samira tv واجريدت الد ا رسدة علدى عيندة مدن النسداء الماكثدات فدي البيدت بولايدة الأغدواط والبدال عددددهن 81 امد أ رة، وتدم الاسدتعانة بدالمنهج الوصدفي واداة جمدع البياندات الاسدتبيان وتم الوصول الى النتائج التالية: هنداك مجمدوت مدن الدددوافع دفعدت بالنسداء الماكثدات فدي البيدت لمشداهدة قنداة ابرزهددا تعلدم حدرف جديددة كدالطب والخياطددة كدون هدذه القنداة SAMIRA.TV تخدا النسداء ومعظدم ب ا رمجهددا خاصدة بالخياطدة والطدب وصدنع الحلويدات ومدن الدددوافع أيضددا حدب النسداء الاطددلات علدى العدالم الخدارجي كدونهم نسداء ماكثدات فدي البيدت وقليلدو الخدرو الدى الفضداء العدام فوجدددوا فدي القنداة المخدر مدن اجدل متابعدة جديدد العدالم والنسداء وجديددد الاخبددار وجديدد الموضدة والجمدال وغيرهددا مدن المواضديع التي تهتم بها النساء . Study summary: Our study aimed to identify the motives behind the exposure of women staying at home to private satellite channels, and this Samira TV channel came as a model? The study started from the problem of what are the motives for the exposure of women staying at home to the satellite channel Samira TV? The study was conducted on a sample of 80 women staying at home in the state of Laghouat. The descriptive method and the questionnaire were used, and the following results were obtained: There are a number of motives that prompted women staying at home to watch the SAMIRA.TV channel, the most prominent of which is learning new crafts such as cooking and sewing, since this channel is for women and most of its programs are for sewing, cooking and making sweets. Among the motives are also women’s love to see the outside world because they are women who stay at home and go out to space. They found in the channel the director in order to follow the new world, women, new news, new fashion, beauty and other topics of interest to women.
SAMIRA TV د ا رسة وصفية لقناة